Clinical Evidence of Interaction between Nutraceutical Supplementation and Platinum-based Chemotherapy - Cocetta, Veronica; Tinazzi, Mattia; Giacomini, Isabella; Rosato, Benedetta; Ragazzi, Eugenio; Berretta, Massimiliano; Montopoli, Monica (Current Medicinal Chemistry, 2023)
Platinum agents, which include cisplatin, oxaliplatin and carboplatin, are chemotherapeutic drugs that represent the first-line treatment for different types of solid tumors, such as ovarian, head and neck, testicular, and bladder cancers. Their beneficial effect is limited by the onset of drug resistance and severe toxicities, involving mainly ototoxicity, neurotoxicity and nephrotoxicity. Recent studies highlight the supplementation of herbal products, vitamins and minerals with antioxidant properties to prevent and protect from side effects. In particular, the introduction of nutraceuticals associated with chemotherapy has improved the patients’ quality of life. However, if from one side, complementary and alternative medicine ameliorates chemotherapeutics-induced toxicities, from the other side, it is important to take into consideration the possible interference with drug metabolism. This review aims to consider the current literature focusing on clinical trials that report an association between nutraceutical supplementation and platinum- based chemotherapy to prevent toxicities, highlighting both beneficial and side effects.
Keywords: Platinum agents